Proteins oxidation and autoantibodies' reactivity against hydrogen peroxide and malondialdehyde -oxidized thyroid antigens in patients' plasmas with Graves' disease and Hashimoto Thyroiditis. (25th June 2017) - Mseddi, Malek; Ben Mansour, Riadh; Gargouri, Bochra; Mnif, Fatma; El Ghawi, Samir; Hammami, Boutheina; Ghorbel, Abdelmonem; Abid, Mohamed; Lassoued, Saloua
Abstract: The aim of this study was to evaluate proteins oxidation in plasmas of two autoimmune thyroid diseases (AITD): Graves' disease (GD) and Hashimoto Thyroiditis (HT), and to determine whether oxidative modification of thyroid antigens (T.Ag) enhanced the reactivity of autoantibodies in plasmas of AITD patients compared with the reactivity towards native T.Ag. Carbonyl and thiol groups and MDA-protein adducts were assessed spectrophotometric methods in plasmas of 74 AITD patients and 65 healthy controls. The reactivities immunoglobulin (Ig)G autoantibodies towards malondialdéhyde (MDA)-modified T.Ag, hydrogen peroxide (H2 O2 )-modified T.Ag, native T.Ag and native derm were checked by enzyme-linked immunosorbent assay (ELISA). Evaluation of oxidized proteins exhibited high levels of MDA bound to proteins and carbonyl groups, as well as reduced thiol level in plasmas of AITD patients by comparison to healthy controls (p < 0.05). The ELISA test showed that AITD patients' plasmas' reactivity to native T.Ag was significantly increased to the reactivity towards native derm, whereas, no differences were found in the reactivity to native T.Ag and derm in controls plasmas. In addition, treatment of T.Ag by oxidants revealed enhanced reactivity of IgG circulating autoantibodies against H2 O2 -oxidized T.Ag compared to native ones (p < 0.001) in plasmas of both AITD. Also, reactivity's to MDA-oxidized T.Ag in GD plasmas decreased compared to native ones (p < 0.05) and no changes were noted for HT. Pearson correlation study resulted in positive correlation between reactivity's to H2 O2 -oxidized T.Ag and free triodotyronine level in GD patients (r = 0.42, p < 0.05) in one hand and thyroid stimulating hormone level in HT patients in the other (r = 0.65, p < 0.001). The data suggest that high production of H2 O2 probably occurred during hormone synthesis could contribute to protein oxidation in AITD and to create neoepitopes responsible for autoantibody reactivity's to H2 O2 -oxidized T.Ag enhancement. These results provide support to the involvement of oxidative stress in AITD development and/or exacerbation. Graphical abstract: Highlights: Protein oxidation was evidenced in autoimmune thyroid diseases. H2 O2 induces enhanced reactivity to oxidatively modified thyroid antigens. Malondialdehyde modification is inadequate to enhance reactivity to thyroid antigens. High production of H2 O2 may cause exacerbation of autoimmune thyroid diseases.